Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Survival, rarity, and extinction in tropical stony corals - Bryan Wilson; Peter J. Edmunds (Conservation Biology, 2026)
Many reef‐building tropical corals are becoming rare. We considered the meaning of rarity in corals and highlighted taxa that have reached low abundances in the last few decades. The difficulties of quantifying rarity in the marine environment arise from the sheer scale and 3‐dimensional nature of the biome and the inherent challenges therein of ecological surveys with scuba. To meet the demands of coral conservation biology in the 21st century, we suggest that contemporary studies of coral communities will require enhanced capacity to identify species and a species‐specific focus on corals occurring at low abundances, which traditional ecological approaches to quantifying populations of benthic marine organisms have a limited capacity to address. Now is the time to revise scientific approaches to respond to the challenges posed by the need to understand and protect rare tropical corals.

Hazard assessment of insecticidal proteins representing different structural classes using an in vitro experimental platform of human intestinal epithelial monolayers - Cindi S. Zimmermann; Sujatha Rajeev Thundivalappil; Brittany Wilson-Mifsud; Sydney Boyle; Yiwei Wang; Ian Lamb; Matthew Merrell; Carey A. Mathesius; Melissa N. Fallers; JoAnna Bultman; Brenda L. Smith; Anne B. Carlson; et al. (Food and Chemical Toxicology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Case Studies on the Use of Patient-centric Sampling for Clinical Studies in Pharmaceutical Drug Development - Shefali Patel; Mike Baratta; Peter Bryan; Hagit Kopel; Steve Lowes; Lina Luo; Neil Spooner; Hans Stieltjes; Katty Wan; Enaksha Wickremsinhe; Amanda Wilson (The AAPS Journal, 2025)

Variable photosystem II thermal stress responses of reef-building corals Pocillopora indiania and Heliopora coerulea across latitudes from the Mascarene Plateau, Indian Ocean - Vikash Munbodhe; Sundy Ramah; Deepeeka Kaullysing; Shakeel Yavan Jogee; Mariette Dine; Bryan Wilson; Ranjeet Bhagooli (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Case Studies on the use of Microsampling for Nonclinical Studies in Pharmaceutical Drug Discovery and Development - Shefali R. Patel; Jason Barricklow; Peter Bryan; Chiara Rospo; Neil Spooner; Ming Wang; Joleen T. White; Amanda Wilson (The AAPS Journal, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Evaluation of an in vitro experimental platform of human polarized intestinal epithelial monolayers for the hazard assessment of insecticidal proteins - Cindi S. Zimmermann; Ryan F. Snow; Brittany Wilson-Mifsud; Kristine LeRoy; Chad Boeckman; Emily Huang; Carey A. Mathesius; Jason M. Roper; Bryan P. Hurley (Food and Chemical Toxicology, 2023)

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Effects of Orally Administered Cannabidiol on Neuroinflammation and Intestinal Inflammation in the Attenuation of Experimental Autoimmune Encephalomyelitis - Nicholas Dopkins; Kathryn Miranda; Kiesha Wilson; Bryan L. Holloman; Prakash Nagarkatti; Mitzi Nagarkatti (Journal of Neuroimmune Pharmacology, 2022)

Mapping Seafloor Relative Reflectance and Assessing Coral Reef Morphology with EAARL-B Topobathymetric Lidar Waveforms - Nicholas Wilson; Christopher E. Parrish; Tim Battista; C. Wayne Wright; Bryan Costa; Richard K. Slocum; Jennifer A. Dijkstra; Matthew T. Tyler (Estuaries and Coasts, 2022)
Topobathymetric lidar is becoming an increasingly valuable tool for benthic habitat mapping, enabling safe, efficient data acquisition over coral reefs and other fragile ecosystems. In 2014, a novel topobathymetric lidar system, the Experimental Advanced Airborne Research Lidar-B (EAARL-B), was used to acquire data in priority habitat areas in the U.S. Virgin Islands (USVI), spanning the 0–44-m depth range. In this study, new algorithms and procedures were developed for generating seafloor relative reflectance, along with a suite of shape-based waveform features from EAARL-B. Waveform features were then correlated with percent cover of coral morphologies, domed and branched, and total cover of hard and soft corals. Results show that the EAARL-B can be used to produce useful seafloor relative reflectance mosaics and also that the additional waveform shape-based features contain additional information that may benefit habitat classification—specifically, to aid in distinguishing among hard corals and their coral morphologies, domed and branched. Knowing the spatial extent of changes in coral communities is important to the understanding of resiliency of coral reefs under stress from human impacts.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Playbacks of food-associated calls attract chimpanzees towards known food patches in a captive setting - Lisa R. O’Bryan; Susan P. Lambeth; Steven J. Schapiro; Michael L. Wilson (Primates, 2021)

Editorial: Coral Reefs in the Anthropocene – Reflecting on 20 Years of Reef Conservation UK - Dominic A. Andradi-Brown; Anastazia T. Banaszak; Thomas K. Frazer; Hannah Gilchrist; Alastair R. Harborne; Catherine E. I. Head; Heather J. Koldewey; Emma Levy; Kirsty Richards; Rebecca Short; Michael Sweet; Kristian Teleki; et al. (Frontiers in Marine Science, 2020)

Locating and eliminating feral swine from a large area of fragmented mixed forest and agriculture habitats in north-central USA - Richard M. Engeman; Bradley E. Wilson; Scott F. Beckerman; Justin W. Fischer; Doug Dufford; James Bryan Cobban (Environmental Science and Pollution Research, 2019)

Resting Stage of Plankton Diversity from Singapore Coastal Water: Implications for Harmful Algae Blooms and Coastal Management - Aurore Trottet; Bryan Wilson; Genevieve Sew Wei Xin; Christaline George; Lemuel Casten; Claire Schmoker; Nurul Syazana Binte Modh Rawi; Moon Chew Siew; Ole Larsen; Hans S. Eikaas; Karenne Tun; Guillaume Drillet (Environmental Management, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Changes in Marine Prokaryote Composition with Season and Depth Over an Arctic Polar Year - Bryan Wilson; Oliver Müller; Eva-Lena Nordmann; Lena Seuthe; Gunnar Bratbak; Lise Øvreås (Frontiers in Marine Science, 2017)

Incorporating climate change into ecosystem service assessments and decisions: a review - Rebecca K. Runting; Brett A. Bryan; Laura E. Dee; Fleur J. F. Maseyk; Lisa Mandle; Perrine Hamel; Kerrie A. Wilson; Kathleen Yetka; Hugh P. Possingham; Jonathan R. Rhodes (Global Change Biology, 2017)
Climate change is having a significant impact on ecosystem services and is likely to become increasingly important as this phenomenon intensifies. Future impacts can be difficult to assess as they often involve long timescales, dynamic systems with high uncertainties, and are typically confounded by other drivers of change. Despite a growing literature on climate change impacts on ecosystem services, no quantitative syntheses exist. Hence, we lack an overarching understanding of the impacts of climate change, how they are being assessed, and the extent to which other drivers, uncertainties, and decision making are incorporated. To address this, we systematically reviewed the peer‐reviewed literature that assesses climate change impacts on ecosystem services at subglobal scales. We found that the impact of climate change on most types of services was predominantly negative (59% negative, 24% mixed, 4% neutral, 13% positive), but varied across services, drivers, and assessment methods. Although uncertainty was usually incorporated, there were substantial gaps in the sources of uncertainty included, along with the methods used to incorporate them. We found that relatively few studies integrated decision making, and even fewer studies aimed to identify solutions that were robust to uncertainty. For management or policy to ensure the delivery of ecosystem services, integrated approaches that incorporate multiple drivers of change and account for multiple sources of uncertainty are needed. This is undoubtedly a challenging task, but ignoring these complexities can result in misleading assessments of the impacts of climate change, suboptimal management outcomes, and the inefficient allocation of resources for climate adaptation.

Relationship between cardiac performance and environment across populations of Atlantic salmon (Salmo salar): a common garden experiment implicates local adaptation - Kayla J. Gradil; Shawn R. Garner; Chris C. Wilson; Anthony P. Farrell; Bryan D. Neff (Evolutionary Ecology, 2016)

Coral—the world's most diverse symbiotic ecosystem - Linda L. Blackall; Bryan Wilson; Madeleine J. H. van Oppen (Molecular Ecology, 2015)
Zooxanthellate corals (i.e. those harbouring Symbiodinium ) are the main builders of the world's shallow‐water marine coral reefs. They represent intimate diverse symbioses between coral animals, single‐celled photosynthetic dinoflagellates ( Symbiodinium spp.), other microscopic eukaryotes, prokaryotes and viruses. Crabs and other crustaceans, worms, sponges, bivalves and hydrozoans, fishes, sea urchins, octopuses and sea stars are itinerant members of these ‘rainforests of the sea’. This review focuses on the biodiversity of scleractinian coral animals and their best studied microscopic epi‐ and endosymbionts. In relation to coral‐associated species diversity, Symbiodinium internal transcribed spacer region sequence types tally 10 2 –10 3 or up to ~15 different operational taxonomic units ( OTU s, or putative species at the 97% sequence identity level; this cut‐off was chosen based on intragenomic sequence diversity observed in monoclonal cultures) and prokaryotes (mostly bacterial) total 10 2 –10 4 OTU s. We analysed all publically accessible 16S r RNA gene sequence data and found Gammaproteobacteria were extremely abundant, followed by Alphaproteobacteria. Notably, Archaea were poorly represented and ‘unassigned OTU s’ were abundant in data generated by high‐throughput DNA sequencing studies of corals. We outline and compare model systems that could be used in future studies of the coral holobiont. In our future directions, we recommend a global coral sampling effort including substantial attention being paid to method of coral tissue acquisition, which compartments (mucus, tissue, skeleton) to explore, broadening the holobiont members considered and linking biodiversity with functional investigations.

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain - F. Joseph Pollock; Cory J. Krediet; Melissa Garren; Roman Stocker; Karina Winn; Bryan Wilson; Carla Huete-Stauffer; Bette L. Willis; David G. Bourne (Coral Reefs, 2015)

Gut microbiome composition and metabolomic profiles of wild western lowland gorillas ( Gorilla gorilla gorilla ) reflect host ecology - Andres Gomez; Klara Petrzelkova; Carl J. Yeoman; Klara Vlckova; Jakub Mrázek; Ingrid Koppova; Franck Carbonero; Alexander Ulanov; David Modry; Angelique Todd; Manolito Torralba; Karen E. Nelson; et al. (Molecular Ecology, 2015)
The metabolic activities of gut microbes significantly influence host physiology; thus, characterizing the forces that modulate this micro‐ecosystem is key to understanding mammalian biology and fitness. To investigate the gut microbiome of wild primates and determine how these microbial communities respond to the host's external environment, we characterized faecal bacterial communities and, for the first time, gut metabolomes of four wild lowland gorilla groups in the Dzanga‐Sangha Protected Areas, Central African Republic. Results show that geographical range may be an important modulator of the gut microbiomes and metabolomes of these gorilla groups. Distinctions seemed to relate to feeding behaviour, implying energy harvest through increased fruit consumption or fermentation of highly fibrous foods. These observations were supported by differential abundance of metabolites and bacterial taxa associated with the metabolism of cellulose, phenolics, organic acids, simple sugars, lipids and sterols between gorillas occupying different geographical ranges. Additionally, the gut microbiomes of a gorilla group under increased anthropogenic pressure could always be distinguished from that of all other groups. By characterizing the interplay between environment, behaviour, diet and symbiotic gut microbes, we present an alternative perspective on primate ecology and on the forces that shape the gut microbiomes of wild primates from an evolutionary context.

Transcriptional profiling of two Atlantic salmon strains: implications for reintroduction into Lake Ontario - Xiaoping He; Chris C. Wilson; Kyle W. Wellband; Aimee Lee S. Houde; Bryan D. Neff; Daniel D. Heath (Conservation Genetics, 2015)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Explosive Pleistocene range expansion leads to widespread Amazonian sympatry between robust and gracile capuchin monkeys - Jessica W. Lynch Alfaro; Jean P. Boubli; Link E. Olson; Anthony Di Fiore; Bryan Wilson; Gustavo A. Gutiérrez‐Espeleta; Kenneth L. Chiou; Meredith Schulte; Sarah Neitzel; Vanessa Ross; Doreen Schwochow; Mai T.T. Nguyen; et al. (Journal of Biogeography, 2012)
Aim Capuchin monkey species are widely distributed across Central and South America. Morphological studies consistently divide the clade into robust and gracile forms, which show extensive sympatry in the Amazon Basin. We use genetic data to test whether Miocene or Plio‐Pleistocene processes may explain capuchin species’ present distributions, and consider three possible scenarios to explain widespread sympatry. Location The Neotropics, including the Amazon and Atlantic Coastal Forest. Methods We sequenced the 12S ribosomal RNA and cytochrome b genes from capuchin monkey specimens. The majority were sampled from US museum collections and were wild‐caught individuals of known provenance across their distribution. We applied a Bayesian discrete‐states diffusion model, which reconstructed the most probable history of invasion across nine subregions. We used comparative methods to test for phylogeographic association and dispersal rate variation. Results Capuchins contained two well supported monophyletic clades, the morphologically distinct ‘gracile’ and ‘robust’ groups. The time‐tree analysis estimated a late Miocene divergence between Cebus and Sapajus and a subsequent Plio‐Pleistocene diversification within each of the two clades. Bayesian analysis of phylogeographic diffusion history indicated that the current wide‐ranging sympatry of Cebus and Sapajus across much of the Amazon Basin was the result of a single explosive late Pleistocene invasion of Sapajus from the Atlantic Forest into the Amazon, where Sapajus is now sympatric with gracile capuchins across much of their range. Main conclusions The biogeographic history of capuchins suggests late Miocene geographic isolation of the gracile and robust forms. Each form diversified independently, but during the Pleistocene, the robust Sapajus expanded its range from the Atlantic Forest to the Amazon, where it has now encroached substantially upon what was previously the exclusive range of gracile Cebus . The genus Cebus , as currently recognized, should be split into two genera to reflect the Miocene divergence and two subsequent independent Pliocene radiations: Cebus from the Amazon and Sapajus from the Atlantic Forest.

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”

Identification of plant mitochondrial proteins: A procedure linking two-dimensional gel electrophoresis to protein sequencing from PVDF membranes using a FastBlot cycle - Bryan Dunbar; Thomas E. Elthon; John C. Osterman; Beth A. Whitaker; S. Brian Wilson (Plant Molecular Biology Reporter, 1997)